Numerical simulation of generalized power law blood flow model through different angles of stenosed bifurcated artery / Azyante Erma Abd Aziz, Muhammad Sabaruddin Ahmad Jamali and Zuhaila Ismail - Abd Aziz, Azyante Erma; Ahmad Jamali, Muhammad Sabaruddin; Ismail, Zuhaila (Unit Penerbitan UiTM Kelantan, 2021)
Atherosclerosis is a key occurrence in cardiovascular disease and is the leading cause of death for people worldwide. Atherosclerosis is the narrowing of lumen as a result of plaque deposition which is known as stenosis. Therefore, arteries become constricted as the stenosis continues to enlarge. These conditions will disturb blood flow where the eddies and separation of streamlines near the vessel wall are formed. The study of numerical simulation of generalized power law for non-newtonion model through different angles of a bifurcated artery is considered in this paper. Realizing that the characteristics of blood influence vascular disease, this study was conducted to acquire knowledge on blood flow characteristics such as velocity profile, pressure drop, streamlines and wall shear stress on different angles of stenosed bifurcated artery. Angles of stenosed bifurcated arteries were divided into three: β=150, β=300, and β=600; to study the effect of different angles of stenosed bifurcated artery through a single stenosis. Results were obtained using COMSOL Multiphysics 5.2 which was based on finite element method in two-dimensional (2D) blood flow model in the presence of single stenosis with different angles of stenosed bifurcated artery.